THE INVESTIGATION OF EUPHEMISMS AS A MEANS OF COMMUNICATION IN THE UZBEK LANGUAGE - No‘monova Zebinso Usmonjon qizi (Western European Studies, 2024)
The article gives an overview of euphemisms and the means of communication formed in Uzbek speech. Specifically, the interrelated aspects of taboos and euphemisms are expressed, as well as the rational use of euphemisms in terms of speech culture.
Keywords: taboo; euphemisms; euphemisms as a means communication